Economic Influence of Cooperatives of Small Farmers from The Southern Macro-Region of Peru with Distributors and Exporters on Agricultural Exports to Brazil by Land - Miguel PANEZ – BENDEZU (Communications of International Proceedings, 2022)
Belonging to the regional value chains would represent an opportunity to obtain a greater participation in the global value chain in the future for developing countries like Peru. In this context, the study aims to determine how the associativity and cooperation of small farmers from the southern macro-region of Peru with distributors and exporters influence agricultural exports to Brazil by land. This research is a mixed method correlational design. The survey and the in-depth interview were used as techniques, and a questionnaire and an in-depth interview guide applied to seventeen experts in international trade, agricultural trade and regional development were used as instruments. The results indicate associativity and cooperation of small farmers in the southern macro-region of Peru with distributors and exporters influence agricultural exports to Brazil by land. In conclusion, associativity and cooperation of small farmers from the southern macro-region of Peru with the distributors and exporters of the southern macro-region of Peru influence agricultural exports to Brazil by land through the export channels, relationship channel and delivery channel. More specifically, a higher proportion of direct exports to foreign distributors over total exports, a higher proportion of direct exports to foreign retailers as a percentage of total exports, a higher proportion of indirect exports to distributors in the country, less degree of dependence of the producer on the buyer and less delivery time of the products to the export market, allows small farmers to increase their agricultural exports.
Keywords: cooperatives; agricultural trade; small farmer; Peru; Brazil